(3GdWH GdfHhj (B/s - (3GHf bje GdLhRjI, CHj YHO Gddg eMeO Hf CHj HcQs; (3bdYLj, YHO GdeYWj Cejfs ([(3GdQjGV(B] :s (3OGQ YGde GdcJH ddWHGYI hGdfTQ hGdJhRjY,s, 2001)
(3GdebOeI hJQLeI GdeUfa(B.s
Keywords: (3GdWH GdfHhjs; (3KbGaI ESdGejIs